1987
DOI: 10.1007/bf00048663
|View full text |Cite
|
Sign up to set email alerts
|

Sediment-associated contaminants ? an overview of scientific bases for developing remedial options

Abstract: The review article covers three major aspects of scientific research on sediment-associated contaminants during the last 20 years: (i) identification and monitoring of sources and distribution (sampling; sample preparation; analyses, mainly of non-residual fractions; estimation of pollution potential); (ii) study of processes and mechanisms of pollutant transfer (interactions between dissolved and particulate element species; particle environments; transport and diagenesis: colloids; surface microlayers; parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(10 citation statements)
references
References 153 publications
(130 reference statements)
0
9
0
Order By: Relevance
“…In fact, the fraction F3 in SIII was second in descending order presented above, other than S0. Accordingly, Förstner (1987) reported the existence of a time-dependent intensity adsorption compounds and suggested that the adsorption sites high energy (less numerous) are filled first, and become limiting in few, and that all the energy of the sediment decreases as these sites are filled less energy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the fraction F3 in SIII was second in descending order presented above, other than S0. Accordingly, Förstner (1987) reported the existence of a time-dependent intensity adsorption compounds and suggested that the adsorption sites high energy (less numerous) are filled first, and become limiting in few, and that all the energy of the sediment decreases as these sites are filled less energy.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with Förstner studies in 1987, the mercury solubility in the water is increased by the amount of decomposed organic matter (Förstner 1987). A great percentage of it is removed by biological processes, what consequently cause a microbial growth and a consumption of the oxygen dissolved in the liquid mass (Wren et al 1991;Jordão et al 2002).…”
Section: Resultsmentioning
confidence: 51%
“…This is due to the fact that aquatic organisms are capable to concentrate the trace elements in up to 105 times the concentration observed in the environment (Hylander et al 2000;Cooper and Gillespie 2001). It is already known that Hg concentration in an organism cannot be considered as a constant value, but as a subjected factor for the influences of the biotic variations as well as abiotic influences (Förstner 1987).…”
Section: Introductionmentioning
confidence: 99%
“…[64][65][66] In this case, the saturation of dissolved oxygen in the SEPAPM can also influence the content of the metals associated with the SPM, which has been verified in other river systems under oxide conditions, where Cd, Zn and Ni were associated with Mn/Fe oxides. 67 For example, Pb and Cu exhibit low mobility due to their affinity with the OH-(hydroxyl) functional group present on the surfaces of kaolinite, oxide, oxyhydroxides, and Fe and Al hydroxides, 68,69 which are found in the region and whose concentrations are controlled by erosion and natural leaching. 70 The control of Pb mobility is also associated with pH and high OM contents, 71 as observed in the SEPAPM, which has alkaline pH values (mean of 7.77) and OM contents between 20.97 and 41.42%.…”
Section: Metals and Arsenic Associated With Spmmentioning
confidence: 99%